EVALUASI PELAKSANAAN PROGRAM KESEHATAN REPRODUKSI DAN SEKSUAL CALON PENGANTIN - Murni, Hasrah; Yatim, Darmayanti; Mesalina, Rosa (Poltekkes Kemenkes Bandung, 2025)
Reproductive and sexual health services for brides-to-be are not evenly distributed at global, national,and regional levels. There are still problems of disparity, quality, and accessibility. The unavailability of policies that regulate the implementation of services is the main obstacle to program implementation.This service is important to reduce the risk of sexually transmitted diseases and pregnancy complications. The government has made efforts to address this through reproductive and sexual health services for cats by improving quality standards and accessibility of services. The study aimed to analyze the implementation of the Reproductive and Sexual Health KIE program for Brides-to-be. This study was a qualitative phenomenological research with the evaluation of the Stuflebeam model program that describes the effectiveness and efficiency of the program holistically. A sample of 16 people was taken by purposive sampling. The data was analyzed with SWOT analysis which became the subject of discussion by the panelists in the decision-making strategy. This research found an important theme,namely the absence of policies that significantly affect the implementation of the program. The results of the SWOT analysis are known to place the organization's position in quadrant 1, a strategy taken by the growth oriented strategy through the innovative model of Catin Sehat Bahagia, Generasi Hebat, Indonesia Maju which supports the pillar of primary service transformation to strengthen preventive promotive activities. Reproductive health services are in a favorable situation,local governments need to develop clear and structured regulations to strengthen the KIE program. Supportive policies will improve access to reproductive health information research.